Osteossíntese de úmero por xenoenxerto ósseo preservado em glicerina 98% ou mel em pombos domésticos (Columba livia) - Gaiga, Leandro Haczkiewicz (2002)
In this study an osteosynthesis technique of transverse humeral fractures diaphysis with use of preserved canine fibula or tibia was evaluated in pigeons by clinical, histologic and radiographic observations. Twenty eight pigeons, weighting between 280 and 380g were separeted in two groups. In the group I, the fibula or tibia were preserved in glicerin 98%, and in the group II were preserved in honey. Anesthesia was induced using butorfanol tartarate and mainteined with halothane. A transverse right midshalft humeral fracture was created using an oscillating bone saw. The fracture was reduced, and the xenografts were inserted intramedullary and associated with cerclage wire. The mean + standart deviation for bone healing were 41 + 4,74 days for both groups. The mean + standart deviation for flight capability were 24,81 + 3,65 days for both groups. More fast bone resorption and least inflamatory response occured in the xenograft preservated in honey. The surgical technique proposed is apropriated for humeral fractures in domestic pigeons (Columba livia) and is preferible the use of xenograft preservated in honey. The results of this study showed that the honey is better than glicerin in the preservation of xenografts.